50.1k views
5 votes
Which of the following is a equivalent form of the equation

Which of the following is a equivalent form of the equation-example-1
User Zeantsoi
by
6.3k points

1 Answer

7 votes

Answer:


c.\ \ \ \ y=(x-a)(x+b)

Explanation:

-The equation
y=x^2-ax+bx-ab can be simplified by grouping like terms together:


y=x^2-ax+bx-ab\\\\\#Group \ terms \ with \ x \ and \ a\\\\\\=x^2+bx-ax-ab

#we then introduce brackets:


x^2+bx-ax-ab\\\\x(x+b)-a(x+b)\\\\\\(x-a)(x+b)

we equate to y:


y=(x-a)(x+b)

Hence, the equitation's equivalent form is
y=(x-a)(x+b)

User Fatou
by
6.2k points